Emotional stress as a cause of syncope and torsade de pointes in patients with long QT syndrome - Vukmirović, Mihailo Čedomir; Vukmirović, Irena Tomašević; Angelkov, Lazar; Vukmirović, Filip (Vojnosanitetski pregled, 2015)
Introduction. Long QT syndrome (LQTS) is a disorder of myocardial repolarization characterized by the prolongation of QT interval and high risk propensity of torsade de pointes (TdP) that can lead to syncope, cardiac arrest and sudden death. Episodes may be provoked by various stimuli depending on the type of the condition. Case report. A 25-year-old famele patient was hospitalized due to syncope that occurred immediately after her solo concert, first time in her life. The patient studied solo singing and after intensive preparations the first solo concert was organized. Electrocardiography (ECG) on admission registered frequent ventricular premature beats (VES), followed by polymorphic ventricular tachycardia – TdP that degenerated into ventricular fibrilation (VF). After immediate cardioversion magnesium and beta-blockers were administered. TdP was registered again several times preceded by VES. The corrected QT interval (QTc) was 516 msec. For secondary prevention of sudden cardiac death, a cardioverter defibrillator was implanted, and beta-blockers continued. After a 1-year follow-up there were no recurrent episodes of TdP, and measured QTc was reduced to 484 msec. Conclusion. Patients with syncope following intensive emotional stress should be evaluated for malignant arrhythmias in the context of LQTS.
Keywords: syncope; stress; psychological; torasades de pointes; drug therapy; electrophysiologic techniques; cardiac